Impacts and Effective Communication on Generation Z in Industrial Revolution 4.0 Era - TALHAH AJMAIN (JETAL: Journal of English Teaching & Applied Linguistic, 2020)
Generation Z (Gen Z), those who were born between the mid-1990s until mid-2000s are closely related to the emerging Indistrial Revolution 4.0 (IR 4.0) era. Both positive and negative impacts towards the social development and communication of Gen Z are apparent. The purpose of this study is to descibe the influence of technology on Gen Z and to discuss the effective means of communication when interacting with this group of people. A systematic review and documentational analysis approach is adopted. The outcome of this study indicated that advancement in technology has hugely affected the social communication skills of Gen Z. It is suggested that the means of approaching this generation requires comprehending their way of thinking, communicating with them in their “tech-language”, and to always be updated with the advancement of information technology (IT), thus ensuring relevance to be in their environment. All these requires groundwork efforts to have direct interaction with them according to the ways of Gen Z.